Analisis Tata Kelola Pemerintahan Desa untuk Meningkatkan Efektifitas Pengelolaan Dana Desa di Indonesia - Intan Puspitasari (Pusat Riset dan Inovasi Nasional, 2025)
This study discusses the analysis of good governance in village government to improve the efficiency of village fund management in Indonesia. The researcher uses a qualitative approach using literature studies to explain the theory and implementation of good governance in the context of village fund management in village government. The researcher compares the theory and findings of previous researchers as an effort to provide scientific solutions and recommendations in the application of good governance principles in efforts to manage clean and responsible village funds in order to improve people's welfare as part of a strategic national development program, especially in rural areas. The result is transparency, accountability and community participation in improving the effective management of Village Fund Allocation. This means that increasing transparency, accountability and community participation will improve the management of effective and clean village fund allocation and realization so that development programs can be enjoyed by the community.